Monismus und Dualismus in Platons Prinzipienlehre - Halfwassen, Jens (Bochumer philosophisches Jahrbuch für Antike und Mittelalter, 1997)
One of the main problems of Plato's unwritten doctrine has to do with whether his theory of principles has a strictly dualistic or rather a more monistic character. The thesis of this essay is that Plato combines monism and dualism in a particular fashion. Both the dialogues and the - testimony of the unwritten doctrine reveal that in Plato's metaphysics the One is the genuinely absolute principle; Plato's second principle, the Many, is not a second absolute - otherwise it would dissolve the very concept of the absolute. Instead, Plato conceives the principle of multiplicity - itself as a unity, therefore as in some - in any event ineffable - way as being derived or having emanated from the absolute One. The One itself is wholly transcendent and thus ineffable, knowable neither by reason nor by intellective intuition. Nonetheless, being and knowledge are constituted - by the coordination of the One and the Many, for which reason the latter is a principle. Hence, Plato's metaphysics combine a monistic ascent to the absolute with a dualistic derivation of being, a combination made necessary because the One transcends not only all being, but also all knowledge.